2021
DOI: 10.3390/su13169144
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Self-Reported Risky Riding Behavior of Motorcyclists at Unsignalized Intersections for Sustainable Transportation

Abstract: In Malaysia, as more than 50% of road collisions involve motorcyclists, the traffic safety of motorcyclists is critical and must be given priority. This study aims to understand the effects of attitudes, social influences, and control factors on the risky riding behavior of motorcyclists at unsignalized intersections in Malaysia. A motorcyclist-riding-behavior survey was conducted to collect and analyze the self-reported risky riding behaviors of motorcyclists. Three main analyses, namely, frequency and percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(80 reference statements)
3
3
0
Order By: Relevance
“…In general, the crosstabulation results between gender and risky riding behaviours revealed that male riders are more aggressive than female riders. This finding conforms with the conclusion by [18]. Many studies have shown that adolescents tend to perform risky behavior than adults.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the crosstabulation results between gender and risky riding behaviours revealed that male riders are more aggressive than female riders. This finding conforms with the conclusion by [18]. Many studies have shown that adolescents tend to perform risky behavior than adults.…”
Section: Discussionsupporting
confidence: 93%
“…According to [8], young drivers are more prone to traffic-law violations, speeding, and more often engaging in risky behaviour. Furthermore, [18] mentioned those young riders are poor in engaging in safe riding behaviour. Therefore, in general, adolescent or young riders more frequently perform risky riding behaviours than adults or older riders.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of participants who engaged in counterflow riding behavior are 21 -45 years old, which falls into the young adult category [40]. This finding aligns with study by Susilo et al [12] and Goh et al [23], where young adult motorcyclists were found to be more inclined to partake in risky riding behaviors. Furthermore, the majority of motorcyclists who engage in counterflow riding behavior were male rather than female.…”
Section: Discussionsupporting
confidence: 82%
“…Novice riders are willing to violate traffic because of cognitive impulsivity [15]. In accordance with that, research by Leong et al [12] found that motorcyclists with 1 to 5 years of riding experience are more likely to engage in risky riding behaviors.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation